2008
DOI: 10.1007/s00464-007-9735-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy: the clinical practice guidelines of the European Association for Endoscopic Surgery (EAES)

Abstract: Despite a lack of level 1 evidence, LS is a safe and advantageous procedure in experienced hands that has displaced open surgery for almost all indications. To support the clinical evidence, further randomized controlled trials on different issues are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
255
0
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(276 citation statements)
references
References 186 publications
3
255
0
18
Order By: Relevance
“…Although the European Association for Endoscopic Surgery guidelines consider portal hypertension as an absolute contraindication for LS (33), several publications since then reported on the safety of the method in patients with cirrhosis and portal hypertension (24,(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Although the European Association for Endoscopic Surgery guidelines consider portal hypertension as an absolute contraindication for LS (33), several publications since then reported on the safety of the method in patients with cirrhosis and portal hypertension (24,(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has traditionally been considered to be a contraindication for LS. 11 Recently, LS has been increasingly indicated for splenomegaly, owing to advances in laparoscopic devices such as harmonic scalpel, ligasure vessel sealing system and endoscopic vascular stapler, and improvements in surgical procedures. [12][13][14][15][16] It has been reported that LS was feasible and is associated with a lower morbidity and shorter hospital stay than OS in patients with splenomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…La Asociación Europea de Cirugía Endoscópica (European Association for Endoscopic Surgey, EAES) ha definido la EL con puertos múltiples como el método de referencia para las enfermedades quirúrgicas con bazos normales a moderadamente agrandados. 1 En un metanálisis de Winslow y Brunt 15 se observó que, a pesar de su mayor duración, la EL con puertos múltiples estuvo asociada con una hospitalización posquirúrgica más breve, tasas inferiores de complicaciones y menores complicaciones pulmonares, infecciosas y con la herida. En otras revisiones sistemáticas 16,17 también se observó la superioridad de la EL sobre la esplenectomía abierta convencional.…”
Section: Discussionunclassified
“…Paralelamente a este aumento, también se han popularizado las esplenectomías con diversas técnicas y resultados quirúrgicos. [1][2][3][4][5][6] La esplenectomía laparoscópica (EL) en la población pediátrica está en general aceptada como un procedimiento técnicamente complejo que requiere de experiencia. [7][8][9][10][11] Si bien es un procedimiento ampliamente utilizado, los estudios que analizan los resultados de las EL hallados en la bibliografía no son concluyentes.…”
Section: Introductionunclassified